Aktivitas Fisiologis dan Pertumbuhan Melon (Cucumis melo L.) pada Perlakuan Sonic bloom dan Pupuk Daun - Handoyo, Gani Cahyo; Endang Setia Muliawati; Ida Rumia Manurung; Muji Rahayu; Ana Farah Rafidah; Rissa Kurnia Anggraini (Jurnal Hortikultura Indonesia, 2025)
Melon is a high-value economic commodity with broad market demand. However, melon production in Indonesia has shown relatively slow growth. To address this issue, sonic bloom technology, which stimulates stomatal opening, can be combined with foliar fertilizer to enhance melon growth. This study aimed to determine the optimal sonic bloom frequency and foliar fertilizer concentration to improve melon plant physiological activity and growth. The research was conducted from January to April 2024 at the Faculty of Agriculture Universitas Sebelas Maret screen house. The experimental design followed a fully nested layout with two treatment factors: sonic bloom frequency (Hz) (F1 = 4,000 and F2 = 4,500) and compound foliar fertilizer application (control, 1, 3, and 5 g L-1). The fertilizer concentration factor was nested within the frequency factor and replicated four times in a randomized arrangement. Data were analyzed using 5% ANOVA, 5% Least Significant Difference (LSD) for mean comparison, and regression and correlation analyses. The results demonstrated that a 4,500 Hz frequency significantly increased chlorophyll b content, plant height at 5 WAP (weeks after planting), and number of segments at 5 WAP. . However, sonic bloom frequency had no significant effect on stomatal density, stomatal conductance, photosynthetic rate, chlorophyll a, total chlorophyll, or leaf number at 5 WAP. The regression analysis results indicated that the optimal foliar fertilizer concentration for enhancing melon growth ranged between 2.96 - 3.68 g L-1.Keywords: chlorophyll, nutrient, photosynthesis, soundwave, stomata